2022
DOI: 10.1097/jom.0000000000002727
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Health-Related Quality of Life and Post–COVID-19 Syndrome in Health Care Workers After SARS-CoV-2 Infection

Abstract: Objectives: The aim of this study is to assess the persistence of symptoms, the prevalence of post-COVID-19 syndrome, and the health-related quality of life (HRQOL) among health care workers (HCWs) 6 months after severe acute respiratory syndrome coronavirus 2 infection. Methods: A prospective cohort study was conducted. All HCWs with confirmed COVID-19 from January to June 2021 were invited to participate. Health-related quality of life was evaluated in three moments: before COVID-19, after COVID-19 (on retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
6
2
1
Order By: Relevance
“…At the baseline measurement, the total prevalence of HADSdepression and HADSanxiety was 50% and 46%, respectively. These results are within the same range as other long-term studies [ 15 , 52 ], indicating a prevalence of depression and anxiety among healthcare workers of up to 44%. In the current study, the included participants were also mostly employed in the healthcare sector.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the baseline measurement, the total prevalence of HADSdepression and HADSanxiety was 50% and 46%, respectively. These results are within the same range as other long-term studies [ 15 , 52 ], indicating a prevalence of depression and anxiety among healthcare workers of up to 44%. In the current study, the included participants were also mostly employed in the healthcare sector.…”
Section: Discussionsupporting
confidence: 89%
“…Comparable prevalence rates were found up to six months after acute infection [ 17 , 50 , 51 ]. Among healthcare workers, depression and anxiety have a prevalence of 8–44% three to ten months after acute COVID-19 [ 15 , 52 , 53 ]. Results regarding the risk factors for higher rates of anxiety and depression are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, results obtained with the specific HRQoL indicator, the EQ‐5D index, were significantly lower in all PCC groups compared with HC group. Lower HRQoL after COVID‐19 has been reported in previous studies 16–19,22–24 . The average EQ‐5D index value for the three groups under investigation exceeded the values previously documented by researchers from the other countries 17,23,24 .…”
Section: Discussioncontrasting
confidence: 50%
“…Studies have documented a decrease in HRQoL and functioning in individuals more than 6 months after discharge or recovery. This has been observed in both patients post‐hospitalization 16–18 and individuals experiencing persistent symptoms 19–24 . Nevertheless, research involving persons experiencing persistent symptoms following moderate or mild COVID‐19 revealed that the average HRQoL fell within the range of the general population mean.…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a grupo profesional, se observaba una mayor afectación de COVID Persistente en los trabajadores asistenciales (en primera línea de actuación sanitaria, más expuestos a la infección por Sars-CoV-2 en este período), versus los no asistenciales. La sintomatología de COVID Persistente más prevalente fue: afectación del sueño, pérdida de memoria, dificultades de concentración, cambios en el estado de ánimo, artralgias, fatiga y cefalea, observados en otros estudios de COVID Persistente (30)(31)(32)(33).…”
Section: Discussionunclassified